A different drummer - Kelley, William Melvin 1937-2017 (riverrun, 2018)
"The month is June 1957. The setting is Sutton, a backwater town in a southern US state. One afternoon, a young black farmer by the name of Tucker Caliban matter-of-factly throws salt on his field, shoots his horse and livestock, sets fire to his house and departs the state; and thereafter the entire African-American population leave with him. The reaction that follows is told across a dozen chapters, each from the perspective of a white townsperson. These range from boys, girls, men, women; who are either liberal, conservative, bigoted or sympathetic - yet who are all grappling with this spontaneous, collective rejection of subordination"--Publisher's description
Keywords: Kelley, William Melvin -- 1937-2017 -- A different drummer; African Americans / Southern States / Fiction; Southern States / Race relations / Fiction; African Americans; Race relations; Southern States; Historical fiction; Satirical literature; Fiction; Fiktionale Darstellung